The universal elements of the Christian religion;: an attempt to interpret contemporary religious conditions - Hall, Charles Cuthbert (The Cole lectures for 1905 delivered before Vanderbilt University, 1905)
The church and the Christianization of the world.--The bearing of sectarian movements upon the Christianization of the world.--The recovery of the apostolic theology.--The Saviour of the world.--The constructive office of Biblical criticism.--The larger church of Christ.